Modernizing irrigation operations: spatially differentiated resource allocations - Renault, D.; Makin, Ian W. (International Water Management Institute, 1999)
Presents an improved methodology for evaluating the resource demands necessary for effective canal operations. Includes identification and analysis of three operational domains: vulnerability, sensitivity and perturbation. Enables more cost-effective strategies and procedures for operation, and priorities for rehabilitation or modernization of physical infrastructure.